Implementation of a Sustainable Training System for Emergency in Vietnam - Sunjoo Kang; Hyejin Seo; Binh Duy Ho; Phuong Thi Anh Nguyen (Frontiers Media S.A., 2018)
PurposeThis study analyzed the project outcomes to share lessons regarding the development of an emergency medicine education system in Vietnam.MethodsRetrospective evaluation was implemented using project outcome indicators.ResultsA total of 13 training courses were administered, with the collaboration of international experts in Korea and Vietnam. A total of 23 kinds of emergency medicine education equipment were purchased, and a basic life support (BLS) and two advanced cardiac life support labs were remodeled to provide appropriate simulation training. Throughout the 2 years of the project, nine Vietnamese BLS instructors were approved by the Korea Association of Cardiopulmonary Resuscitation under American Heart Association. Results of evaluation by Korean international development experts were based on five criteria, provided by the Development Assistance Committee of the Organization for Economic Co-operation and Development, were excellent. Success factors were identified as partnership, ownership, commitment, government support, and global networking.ConclusionProject indicators were all accomplished and received an excellent evaluation by external experts. For sustainable success, healthcare policy and legal regulation to promote high quality and safe service to the Vietnamese people are recommended.